Molecular Docking and ADMET Prediction of Bioactive Compounds from Centella asiatica, Coenzyme Q10, and Ethyl Ascorbic Acid Targeting PPAR Receptors as Potential Antioxidant Agents - Nur Khofifah; Dini Khofifah; Ni Luh Dewi Aryani (Jurnal Penelitian Pendidikan IPA, 2026)
Excessive ultraviolet exposure induces oxidative stress that accelerates skin aging, yet effective natural modulators of antioxidant pathways remain limited. This study investigated the potential of bioactive compounds from Centella asiatica, Coenzyme Q10, and ethyl ascorbic acid as PPAR receptor agonists associated with antioxidant regulation. An in silico approach was applied using molecular docking with Molegro Virtual Docker and ADME prediction analysis. Docking performance was evaluated using rerank scores and interaction analysis with key amino acid residues. Coenzyme Q10 and ethyl ascorbic acid isomers showed the most negative rerank scores (−62.08 and −55.65 kcal/mol), indicating strong receptor affinity. Asiaticoside and madecassoside formed extensive hydrogen and steric interactions with Arg284 and His280. ADME analysis revealed that ethyl ascorbic acid exhibited optimal balance between solubility, permeability, and safety. These findings suggest that ethyl ascorbic acid and Coenzyme Q10 are promising candidates for antioxidant therapy through PPAR activation. This study provides computational evidence supporting the development of natural antioxidant agents targeting oxidative stress–related skin damage.